(untitled) (REMUNOM, 2025)
This study analyzes the complex relationship between alcohol consumption, depression, and suicidal behavior, discussing how alcohol can act as a reinforcer of suicidal outcomes in individuals with depressive disorders. This is a bibliographic study, developed through an integrative review of the literature, with a qualitative and descriptive approach. Searches were conducted in the PubMed and Virtual Health Library (VHL) databases, considering publications between 2020 and 2025, using the PICO strategy to guide the selection of studies. The results revealed that alcohol has a direct influence on neurotransmitters such as GABA, dopamine, and serotonin, compromising emotional regulation and increasing impulsivity. Chronic use was associated with dependence, withdrawal syndrome, and worsening depressive symptoms, while acute use favored disinhibition and higher lethality in suicide attempts. The analysis also highlighted the participation of genetic and environmental factors, such as trauma, social vulnerability, and hereditary predispositions, which intensify the relationship between alcohol use disorder (AUD) and depression. It was also observed that the comorbidity between these conditions increases the risk of suicide, especially when there is a lack of psychosocial support and multidisciplinary follow-up. It was concluded that the interaction between alcohol, depression, and suicide is multifactorial and requires an interdisciplinary approach that considers biological, psychological, and social aspects. The study reinforces the need for effective public policies aimed at preventing alcohol abuse, promoting mental health, and strengthening support networks as a way to reduce the risk of self-harm.